2017
DOI: 10.1016/j.jval.2017.08.2544
|View full text |Cite
|
Sign up to set email alerts
|

Title: Modelling The Effect of Syphilis Screening At The Entry Point in Chilean Prisons

Abstract: A869respectivamente. Al analizar por dimensiones, la asociada a dolor fue modificada significativamente entre los grupos. Las diferencias por sexo mostraron que los hombres presentan una desutilidad significativamente mayor que las mujeres con la preparación con Polietilenglicol con electrolitos de 5,1%. La calidad de la preparación fue similar y adecuada para las tres preparaciones analizadas. ConClusions: Los pacientes que son sometidos a preparación intestinal ven afectados su calidad de vida con cualquiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…In total, 22 economic evaluations were included [ 21 40 ]; fifteen had the outcome framed in DALYs [ 21 34 , 41 ], and seven had the outcome framed in QALYs [ 35 40 , 42 ]. Two primary studies were identified after hand-searching reference lists [ 40 , 43 ]. Note that one primary study was also an economic evaluation [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 22 economic evaluations were included [ 21 40 ]; fifteen had the outcome framed in DALYs [ 21 34 , 41 ], and seven had the outcome framed in QALYs [ 35 40 , 42 ]. Two primary studies were identified after hand-searching reference lists [ 40 , 43 ]. Note that one primary study was also an economic evaluation [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two primary studies were identified after hand-searching reference lists [ 40 , 43 ]. Note that one primary study was also an economic evaluation [ 40 ]. Thirteen burden of disease studies were included as part of the review: seven studies as part of the GBD series published by the Institute of Health Metrics and Evaluation [ 4 , 44 – 49 ], four country-related landmark burden of disease studies [ 50 – 53 ], and two other separate burden of disease studies [ 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations